The Relationship Between Sleep Quality and Cardiac Autonomic Modulation According to Physical Activity Levels in Adults: A Cross-Sectional Study - De Moraes-Ferrari, G (Springer Science and Business Media Deutschland GmbH, 2025)
Background: Poor sleep quality has been related to various health issues, particularly cardiovascular diseases. This association is partly due to the negative influence that sleep problems have on cardiac autonomic activity, which is often evaluated heart rate variability (HRV). Regular physical activity (PA) has been suggested as an effective strategy to improve HRV and mitigate the adverse effects of sleep disorders. Although some studies have been conducted in this field, further research is warranted to comprehensively understand how PA influences this dynamic. Aim: To analyse the association between cardiac autonomic modulation (CAM) and sleep quality, stratified by physical activity levels. Methods: The sample consisted of 230 participants. CAM was assessed under resting conditions using time- and frequency-domain indices of HRV: RMSSD, SDNN, LF n.u, HF n.u and nonlinear metrics such as SD1 and SD2. Sleep quality was measured using the Pittsburgh Sleep Quality Index, and PA was objectively quantified with an ActiGraph GT3X accelerometer. Results: Among participants classified as insufficiently active, poor sleep quality was significantly associated with lower parasympathetic activity, reflected in reduced RMSSD (β = -12.10; 95% CI: -21.02 to -3.06) and SD1 (β = -8.39; 95% CI: -14.81 to -1.97) values. No significant associations were found in the physically active group. Conclusions: Lower parasympathetic modulation was observed in insufficiently active individuals reporting poor sleep quality, suggesting that PA may mitigate the unfavorable effects of sleep impairment on cardiac autonomic function. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.
Keywords: Sleep; Autonomic nervous system; Heart rate; Physical activity